A Traditional Chinese Medicine Herb Mixture Qingjie Fuzheng Granules Inhibits Hepatocellular Carcinoma Cells Growth by Inducing Apoptosis - Pingping Zhong PhD (Journal of Evidence-Based Integrative Medicine, 2018)
In this study, hepatocellular carcinoma (HCC) mouse xenograft model, MTT assay, colony formation, nuclear staining, and Annexin-V/PI staining assays were used to evaluate the effect of Qingjie Fuzheng granules (QFG) on cell proliferation and apoptosis of HCC cell in vivo and in vitro. Furthermore, Western blotting was performed to detect the expression of Fas, FasL, Bcl-2, Bax, and the activation of caspase-3/-8/-9. The results showed that QFG reduced tumor weight ( P < .05) but had no effect on body weight gain in HCC mice in vivo. QFG significantly reduced HCC cell viability and attenuated cell proliferation in a dose-dependent manner ( P < .05). QFG increased the expression of Fas, FasL, and Bax ( P < .05). QFG downregulated the expression of Bcl-2 and promoted the activation of caspase-8, -9, and -3 ( P < .05). These results suggested that QFG possessed anticancer effects, and the mechanisms of action may involve the death receptor pathway and mitochondrion-dependent pathway-mediated apoptosis.